FRI0100 COMPARISON OF PATIENTS (PTS) WITH RHEUMATOID ARTHRITIS (RA) AMONG DISEASE ACTIVITY CATEGORIES AFTER 6 MONTHS OF TREATMENT WITH A TUMOUR NECROSIS FACTOR INHIBITOR (TNFI): RESULTS FROM THE CORRONA® RA REGISTRY. (2nd June 2020) - Kremer, J. M.; Winkler, A.; Anatale-Tardiff, L.; Mclean, R.; Shan, Y.; Moore, P.; Tundia, N.; Suboticki, J.; Tesser, J.
Abstract : Background: Targeting remission (REM) or low disease activity (LDA) is a widely accepted treatment strategy for RA. However, there are limited data on the proportion of pts who achieve these targets, or remain in moderate (MDA) or high disease activity (HDA) following advanced therapy. Objectives: To estimate the proportion of RA pts in disease activity states (REM, LDA, MDA, and HDA) who were biologic-naïve at initiation and had continuous treatment with a TNFi for 6–12 months in the Corrona RA registry. Methods: Eligible pts were aged ≥18 years, biologic-naïve, initiated TNFi treatment between January 1, 2010 and July 31, 2019, and had continuous use of a TNFi for 6–12 months. Disease activity was defined based on Clinical Disease Activity Index (CDAI) at the visit closest to 6-month follow-up: REM, ≤2.8; LDA, >2.8–10; MDA, >10–22; and HDA, >22. Disease characteristics, disease activity measures, and pt-reported outcomes (PROs) were reported at TNFi initiation and at the 6-month follow-up visit. Results: 2586 biologic-naïve pts who initiated a TNFi and had continuous use for 6–12 months were included. At TNFi initiation, 167 (6%) were in REM, 479 (19%) had LDA, 907 (35%) had MDA, and 1033 (40%) had HDA. After 6–12 months of treatment, 563 (21.8%) were in REM, 923 (35.7%) had LDA, 674 (26.1%) had MDA, and 426 (16.5%) had HDA. Pts with HDA/MDA at 6–12 months were more likely to have a history of hypertension (32.7% HDA; 34.0% MDA; vs 23.6% REM) and had higher mean body mass index (BMI) (30.9 HDA; 31.1 MDA; vs 29.0 REM) at baseline compared with pts in REM. Disease activity measures and PROs were worse in pts with MDA and HDA vs LDA and REM after 6–12 months (Table). Pt Global Assessment was higher than Physician Global Assessment across all groups. Conclusion: While 57.4% of pts who initiated a TNFi experienced a favorable outcome, >40% required additional or alternative intervention to achieve REM/LDA. Pts who remained in MDA/HDA continued to have an inadequate response to TNFi (as measured by disease activity measures and PROs) after 6–12 months of treatment compared with those who achieved REM/LDA. Disclosure of Interests: Joel M Kremer Shareholder of: May own stocks and opinions, Grant/research support from: Research and consulting fees from AbbVie Inc., Consultant of: AbbVie, Amgen, BMS, Genentech, Inc., Gilead, GSK, Lilly, Pfizer, Regeneron and Sanofi, Employee of: Corrona, LLC employee, Anne Winkler Consultant of: AbbVie, Pfizer, and Novratis, Speakers bureau: AbbVie, Janssen, Sanofi, Genentech, Celgene, Eli Lilly, and Novartis., Laura Anatale-Tardiff Employee of: Corrona, LLC employee, Robert McLean Employee of: Corrona, LLC, Ying Shan Employee of: Corrona, LLC employee, Page Moore Employee of: Corrona, LLC employee, Namita Tundia Shareholder of: May own stocks and options, Employee of: AbbVie employee, Jessica Suboticki Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., John Tesser Consultant of: Sanofi/Regeneron, Speakers bureau: Sanofi/Regeneron